ENHANCING TEACHER SELF-EFFICACY IN SEL: INSIGHTS FROM A SCOPING REVIEW - Ruth E. Ignacio (LPPM UNiversitas Bina Mandiri Gorontalo, 2024)
This scoping review explores the individual and contextual factors that enable teacher self-efficacy for implementing social and emotional learning (SEL) programs in K-12 classrooms. Guided by Bandura's social cognitive theory, the review synthesizes evidence from 10 studies published between 2009 and 2023. Key themes emerged related to professional development and training, teacher characteristics and experience, school climate and leadership support, comfort with SEL practices, teacher-student relationships, SEL competencies and beliefs, and the influence of socio-cultural factors. The findings are organized into a proposed framework categorizing enablers of teacher self-efficacy into personal factors (e.g., social-emotional competence), behavioral factors (e.g., modeling SEL skills), and environmental factors (e.g., access to resources). The review highlights the multidimensional nature of teacher self-efficacy in SEL contexts and suggests that a comprehensive approach addressing multiple levels of influence is needed to create enabling environments. Implications for practice include providing high-quality training, fostering supportive school climates, and investing in teachers' personal development. Limitations and future research directions are discussed.